Knowledge of users of low-dose oral combined contraceptives about the method - Camila Félix Américo; Paula Sacha Frota Nogueira; Rebeca Pinho Romero Vieira; Cleide Gomes Bezerra; Escolástica Rejane Ferreira Moura; Marcos Venícios de Oliveira Lopes (Universidade de São Paulo, 2013)
OBJECTIVES: to identify the knowledge of users of combined oral contraceptive about correct use, side effects and complications; to verify the correlation between knowledge about the method with age, education, family income and time of use. METHOD: cross-sectional study performed in Fortaleza, Ceará, Brazil, from March to July 2010, with 294 women. Data were collected through interviews. RESULTS: 75% had substantial knowledge about the proper use and side effects and no knowledge about complications. The higher the educational level and family income, the higher the women's knowledge about the correct use of the method. Positive correlation suggests that women who used the method for longer knew more about its side effects. CONCLUSION: there are knowledge gaps about the method, which are influenced by socioeconomic variables and use time.